Postoperative Anticoagulants in Preventing Portal Vein Thrombosis in Patients Undergoing Splenectomy Because of Liver Cirrhosis: A Meta-Analysis. Issue 12 (December 2016) - Zhang, Jian-Ying; Wang, Yun-Bing; Gong, Jian-Ping; Zhang, Fan; Zhao, Yong
Portal vein thrombosis (PVT) frequently occurs in patients undergoing splenectomy because of liver cirrhosis. Whether the use of postoperative anticoagulants can decrease the incidence of PVT in these subjects is inconclusive. Moreover, the safety of the use of postoperative anticoagulants in the aforementioned patients is a concern. This meta-analysis aims to explore the effectiveness and safety of the preventive anticoagulants to prevent PVT in patients undergoing splenectomy because of liver cirrhosis. Four English language databases (i.e., PubMed, Embase, Cochrane Library, and Web of Science) and four Chinese language databases (i.e., Wanfang, CNKI, Cqvip, and CBM) were searched for randomized controlled trials, cohort studies, and case-control studies on the use of preventive anticoagulants to prevent PVT in patients undergoing splenectomy because of liver cirrhosis from their inception to September 15, 2015. The primary outcome was postoperative PVT incidence. The secondary outcomes included postoperative complications and adverse reaction. Study-specific odds ratios were combined to calculate pooled value through a fixed effects model. A total of 17 original studies were included, involving 1, 497 patients. This meta-analysis showed that the preventive anticoagulant group had a lower incidence of PVT than the no anticoagulant group (odds ratio, 0.31; 95% confidence interval, 0.23–0.40; P < 0.05). According to the description of limited studies, the upper gastrointestinal hemorrhage mainly occurred in the no anticoagulant group. Meanwhile, the adverse reaction was trivial in the group using anticoagulants, which could easily be released with no special management. Postoperative anticoagulants can effectively decrease PVT incidence in subjects undergoing splenectomy because of liver cirrhosis. These published studies are more prone to show that no serious negative influence of anticoagulants exists in the aspect of safety. However, further studies are still needed.